2017
DOI: 10.1371/journal.pone.0182831
|View full text |Cite
|
Sign up to set email alerts
|

Determination of regulatory ionophore coccidiostat residues in feedstuffs at carry-over levels by liquid chromatography-mass spectrometry

Abstract: In this study samples of feedstuffs were collected from different feed mills and animal farms located in central Italy and analyzed for ionophore coccidiostat residues at carry-over levels by liquid chromatography-mass spectrometry. Since unavoidable cross-contamination of feedstuffs may occur during their production as well as distribution and storage, the collection of samples covered all these different stages. Residues of lasalocid, monensin, salinomycin and maduramicin were detected in 32.4% of samples, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
(24 reference statements)
0
5
2
Order By: Relevance
“…Among ionophoric molecules, the most frequently detected coccidiostat in untreated feed was LAS, found in 11 samples, one of which exceeded the regulatory limit, followed by NAR found in 7 samples of which one was a noncompliant sample (Table 3). These results diverge from those reported by Annunziata et al [1] and Moretti et al [23] who found MON as the most frequently detected carry-over ionophore coccidiostat in feedstuff collected according to Italian NRCP (22% and 35%, respectively).…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Among ionophoric molecules, the most frequently detected coccidiostat in untreated feed was LAS, found in 11 samples, one of which exceeded the regulatory limit, followed by NAR found in 7 samples of which one was a noncompliant sample (Table 3). These results diverge from those reported by Annunziata et al [1] and Moretti et al [23] who found MON as the most frequently detected carry-over ionophore coccidiostat in feedstuff collected according to Italian NRCP (22% and 35%, respectively).…”
Section: Resultscontrasting
confidence: 99%
“…It is to be noticed that the non-compliance rate varies mainly as a result of an increase in samples tested during the years examined, rather than an effective decrease in positive samples. Ionophoric molecules were detected in 28 feed samples (10.4%), while non-ionophoric molecules were found in 54 samples (20.15%); these results differ from those reported by Annunziata et al [1] for ionophoric compounds (32.4%) and are comparable to those reported by the same authors in 2018 [36] for non-ionophoric residues in feed samples (20.3%) collected as part of the official Italian monitoring plan in other regions of Italy. Among ionophoric molecules, the most frequently detected coccidiostat in untreated feed was LAS, found in 11 samples, one of which exceeded the regulatory limit, followed by NAR found in 7 samples of which one was a noncompliant sample (Table 3).…”
Section: Resultscontrasting
confidence: 79%
See 2 more Smart Citations
“…Several studies have reported that feed cross-contamination with a carryover of ionophore coccidiostats has been identified as the most common source of exposure in laying hens ( Kennedy et al, 1996 ; Borràs et al, 2011 ; Rokka et al, 2013 ; Spiegel et al, 2013 ; Roudaut and Fournet, 2017 ; Roila et al, 2019 ). It is widely accepted that under practical conditions in feed mills during the production of medicated and non-medicated feeds in the same line of production, some traces of the medicated feed batch may remain in the production line, and this carryover can contaminate subsequent batches of non-medicated feed ( Kennedy et al, 1996 ; Borràs et al, 2011 ; O'Mahony et al, 2012 ; Annunziata et al, 2017 ). The risk and degree of cross-contamination depend on the equipment and methods used in the feed mill as well as the electrostatic properties of the premix formulation ( HAFEZ, 1991 ; Kennedy et al, 1996 ).…”
Section: Sources Of Exposure In Laying Hens and Incidence Of Occurren...mentioning
confidence: 99%